Knowledge, Intentions, and Barriers to Use Vasectomy Among Married Men in Ethiopia - Hurisa, Tesfaye; Betru, Kaleab A.; Abubeker, Ferid A. (Ethiopian Journal of Reproductive Health, 2022)
Background Among the arrays of permanent contraceptive methods, vasectomy is the least known and used method of contraception. Even when men are aware of vasectomy, their understanding is often incomplete or incorrect. So, the aim of the study was to assess knowledge, intention, and barriers to using vasectomy among married men living in Addis Ababa, Ethiopia. Method A community-based cross-sectional study was conducted on 264 participants in Arada sub-city, Addis Ababa, Ethiopia. Data was collected via face-to-face interviews using a pretested structured questionnaire. Then the data was checked for completeness and entered into SPSS version 26 for analysis. Descriptive analysis with frequencies and percentages was performed to describe the socio-demographic status, intention, and barriers to using vasectomy. A bivariable and multivariable logistic regression model was used to analyze the association between variables. Results Two hundred sixty-four married men were included in this study. The mean age of the study participants was 38.73±10.76. The study showed that the intention to use vasectomy as a method of contraception was reported in 18% of married men. About 51.7% of the participants had good knowledge, and 59.4% had a positive attitude toward the use of vasectomy. In multivariate analysis, participants who had a positive attitude towards vasectomy were 2.1 times more likely to use vasectomy than their counterparts. Conclusion The intention to use vasectomy as a method of contraception among married men in our study was comparable to studies in similar settings. Having a positive attitude towards vasectomy was significantly associated with the intention to use vasectomy for future life. So, engaging in better education that improves the attitude of couples towards vasectomy is essential to enhance the intention of men to use vasectomy. Key Words – Vasectomy, Family Planning, Intention, Barrier, Ethiopia